Masculinity Through Neytiri’s Character in Avatar The Way of Water (2022) Movie By James Cameroon - Anugrah, Jeri; Ana Rosida (Journal of English Development, 2026)
Most cinematic analyses tend to frame strong female characters through the lens of empowerment or feminism. While, this movie embodies traditionally masculine traits without forfeiting their femininity. Therefore, this research aims to find forms of masculinity that displayed by Neytiri’s character in the movie Avatar The Way of Water, using Judith Halberstam’s theory. Through a qualitative descriptive method, the study identifies two key expressions: Butch Femininity, shown in Neytiri’s physical strength, emotional control, and leadership; and Performance of Masculinity, highlighted in battle scenes where she protects her family. The findings indicates that Neytiri challenges conventional gender norms by displaying resilience, bravery, and a strong protective instinct towards her family and community. Her character demonstrates that masculinity is not exclusively tied to men, but also can embodied by women. This study contributes to the growing discourse on gender fluidity in media by highlighting how female characters can embody alternative masculinities in ways that are empowering rather than reductive. By centering female masculinity within a blockbuster film, the narrative opens space for more inclusive and diverse representations of gender in popular culture.